Da arte de se tornar judeu: interpretando estratégias identitárias vivenciadas por comunidades judaicas em Campina Grande/PB - Braga, Mirella de Almeida (2016)
The current dissertation opens a debate about the ethnic and religious borders formation process in/among three Jewish communities active in the city of Campina Grande/PB, drawing attention to determined elements and daily strategies that operate as true milestones of differentiation and identity affirmation. Through description of communitarian events (meetings, rituals and festivities) and the narrative reconstruction of certain life stories of individuals in their social interactions in familiar and religious spaces, this work analyses as the history “jewish cultural resistance” translates itself in little details of thought and action which reveal differentiated “arts of becoming jewish”.